Covered Interest Parity Arbitrage. (18th May 2022) - Rime, Dagfinn; Schrimpf, Andreas; Syrstad, Olav
Abstract: To understand deviations from covered interest parity (CIP), it is crucial to account for heterogeneity in funding costs across both banks and currency areas. For most market participants, the no-arbitrage relation holds fairly well when implemented using marginal funding costs and risk-free investment instruments. However, a few high-rated banks do enjoy CIP-arbitrage opportunities. Dealers avert inventory imbalances stemming from lower-rated banks' usage of FX swaps to obtain dollar funding by inducing opposite (arbitrage) flows from high-rated banks. Arbitrage trades are difficult to scale, however, because funding costs increase as soon as arbitrageurs increase positions. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.